2019
DOI: 10.5194/angeo-37-1223-2019
|View full text |Cite
|
Sign up to set email alerts
|

Energetic electron enhancements under the radiation belt (<i>L</i> < 1.2) during a non-storm interval on 1 August 2008

Abstract: Abstract. An unusual event of deep injections of >30 keV electrons from the radiation belt to low L shells (L<1.2) in the midnight–dawn sector was found from NOAA/POES observations during quiet geomagnetic conditions on 1 August 2008. Using THEMIS observations in front of the bow shock, we found transient foreshock conditions and interplanetary magnetic field (IMF) discontinuities passing the subsolar region at that time. These conditions resulted in generation of plasma pressure pulses and fast … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…However, which electrodynamic process leads to the appearance of sufficiently strong (several mV/m) convection electric field at heights less than 2000 km is still an open question. Additionally, note an interesting fact that many FEE events observed in the absence of geomagnetic storms often occurred during the solar minimum [27]. The authors found that the trigger for such events is local pressure pulses associated with the dynamics of the foreshock in front of the Earth's bow shock.…”
Section: Discussionmentioning
confidence: 99%
“…However, which electrodynamic process leads to the appearance of sufficiently strong (several mV/m) convection electric field at heights less than 2000 km is still an open question. Additionally, note an interesting fact that many FEE events observed in the absence of geomagnetic storms often occurred during the solar minimum [27]. The authors found that the trigger for such events is local pressure pulses associated with the dynamics of the foreshock in front of the Earth's bow shock.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that sometimes the upstream solar wind and IMF can differ from those near the front of the Earth's bow shock, especially it concerns the magnetic field direction along the solar wind flow (radial IMF; e.g., Bier et al, ; Suvorova & Dmitriev, ; Vokhmyanin et al, ; Zastenker et al, ). The near‐Earth THEMIS observations provide reliable information on solar wind and IMF parameters directly affecting the magnetosphere (Suvorova, et al, ).…”
Section: Themis‐c Observations Of the Solar Wind And Imfmentioning
confidence: 99%